PERBANDINGAN PERTUMBUHAN TANAMAN GULMA - Yuliani1, ; Yuni Sri Rahayu1, ; Evie Ratnasari1, ; Mitarlis2, (Matematika dan Sains, 2010)
The aims of research were to know the growth difference between the weeds crop and the cultivation crop after treated by the alelochemical isolated from the leaves of Pluchea indica Less. Plants test for the cultivation crop were green bean and peanut (leguminaceae), tomato and chili (Solanaceae). While for weeds crop were Mimosa pudica and Ruellia tuberosa (leguminaceae), Amaranthus spinosus and Celosia arganteae (Amaranthaceae). Concentration used were 1%, 0.50%, 0.25%, 0.125% and 0%. Design research used was completed randomized design with one factor. Result of research showed that there are differenciate the growth of weeds and cultivation crop after treated using alelochemical isolated from Pluchea indica. For cultivation crop, green bean was very tolerant to alelochemical, followed by chili and tomato. While weeds crop, the best growth was showed by Celosia, followed by Ruellia, Amarantus, and Mimosa. The bigger alelochemical concentration used, the bigger inhibition of growth. The weeds crop was inhibited more bigger than cultivation crop.